Court of the Seven Seas and Tower of the Sun, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
The Court of the Seven Seas looking toward the Tower of the Sun - is a beautiful sight by day - brilliant and magnificent at night. Large murals depicting man's conquest over the seas, grace the facades of the palace walls fronting upon this Court.